2016
DOI: 10.3389/fvets.2016.00002
|View full text |Cite
|
Sign up to set email alerts
|

Development of the Chick Microbiome: How Early Exposure Influences Future Microbial Diversity

Abstract: The concept of improving animal health through improved gut health has existed in food animal production for decades; however, only recently have we had the tools to identify microbes in the intestine associated with improved performance. Currently, little is known about how the avian microbiome develops or the factors that affect its composition. To begin to address this knowledge gap, the present study assessed the development of the cecal microbiome in chicks from hatch to 28 days of age with and without a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

49
257
1
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 259 publications
(314 citation statements)
references
References 38 publications
(44 reference statements)
49
257
1
7
Order By: Relevance
“…Attaining immune functions by GALT in neonate chickens has been associated with the seeding of the GIT with primary microflora, and its evolution to stable climax microflora that assures immune-microbe homeostasis and competitive exclusion of the enteropathogens [56]. The development of the microbial population is strictly age-dependent, which indicates that early stimulation of beneficial microflora is an absolute necessity, as it affects, to a great extent, the entire life-span of an individual [57]. …”
Section: Discussionmentioning
confidence: 99%
“…Attaining immune functions by GALT in neonate chickens has been associated with the seeding of the GIT with primary microflora, and its evolution to stable climax microflora that assures immune-microbe homeostasis and competitive exclusion of the enteropathogens [56]. The development of the microbial population is strictly age-dependent, which indicates that early stimulation of beneficial microflora is an absolute necessity, as it affects, to a great extent, the entire life-span of an individual [57]. …”
Section: Discussionmentioning
confidence: 99%
“…Poultry is the world's primary source of animal protein (FAO, ); the global population of chicken exceeds 40 billion individuals (Oakley, Lillehoj, et al., ). Broiler chicken meat comprises the majority of the poultry meat industry, and ensuring the health and productivity of broilers has become a key aspect of this industry (Ballou et al., ). Recent studies using high throughput sequencing, have shown the role of the gastrointestinal tract (GIT) microbiome in gastrointestinal development, nutrient absorption, and pathogen invasion resistance (Crhanova et al., ; Pan & Yu, ; Park et al., ; Pedroso & Lee, ; Yeoman et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Concurrently, initiatives to control antibiotic use in production animals, especially the restriction in use of growth promoters worldwide to prevent the emergence of antibiotic resistance has made the manipulation of intestinal microbiomes in poultry an attractive alternative to support innate immunity and improve health (Kogut & Arsenault, ; Pedroso & Lee, ), as well as productivity (Singh et al., ). Supplementing the diets of developing broilers with probiotics or applying vaccines have long‐term effects on the broilers’ GIT microbiome composition (Ballou et al., ). In particular, feed additives have altered microbial activity in the GIT as well as disease susceptibility (Engberg, Hedemann, Steenfeldt, & Jensen, ; Mitsch et al., ; Owens, Tucker, Collins, & McCracken, ), but the exact mechanisms responsible for these effects remain unclear (Oakley, Lillehoj, et al., ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations